(untitled) (Collection of scientific works «Modern structures of metal and wood», 2020)
One of the most common structural schemes used in the construction and reconstruction of berths - is a thin wall (bolverk). This system consists of a front wall and an anchor system, which includes a string and an anchor wall (or other type of anchoring device). There are some variations of the design scheme, but each of them includes a front wall of sheet piling. The paper presents options for determining the geometric characteristics of sheet piles for use in the calculations of flat deformation (flat design model). In the standard assortments of sheet piling, only the general geometrical characteristics of the section such as area, moment of inertia, moment of resistance, radius of inertia are given, but this is not enough for use in finite element calculations. The complex shape of the cross-section of the sheet pile (zeta, trough, straight, combined and other types of cross-section) leads to differences in the definition of geometric characteristics and their interpretation in the flat and spatial formulation of the stress-strain state. The paper presents a method for determining the geometric characteristics of the cross section for a bending rod for a flat design model. For finite element calculations, the lost complex for geotechnical calculations Midas GTS NX is used. The use of the finite element method in determining the geometric characteristics of the cross section of the sheet pile gives a relative error of up to 5% relative to the data given in the range. What is acceptable for use in further calculations of berth structures. The paper considers two options for one meter of the running wall: 1 m includes 1 tongue completely 600 mm and the second partially 400 mm; in 1 m both sheet piles on 500 mm enter. The lowest value of the moment of inertia was obtained for the first variant 72511 cm4, which coincides with the value from the range by -0.26%. And for the second option, the moment of inertia is more than 12%. Therefore, the calculations should take the most unfavorable option.